Specimen Size Effect of Interface Strength Distribution Induced by Grain Structure of Cu Line - SUZUKI, Toshiaki; OMIYA, Masaki; NAKAMURA, Tomoji; CHEN, Chuantong; SHISHIDO, Nobuyuki; SUZUKI, Takashi; KOIWA, Kozo; KAMIYA, Shoji; SATO, Hisashi; NOKUO, Takeshi; NISHIDA, Masahiro (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series A, 2013)
A new technique for the evaluation of local interface adhesion energy was applied to the interface between Cu and cap layer in a Cu damascene interconnect structure, which consists of both the interfacial fracture test and the finite-element simulation. After specimens in-plane dimensions of 1×1 μm, 5×5 μm and 10×10 μm fractured by focused ion beam (FIB), the interfacial fracture test was implemented by a novel system with nano-indenter in FIB-SEM dual-beam microscope. With the maximum load measured during the fracture test employed in an elastic-plastic simulation, interface adhesion energy was evaluated and almost equal among all types of specimens. On the other hand, the variation of the evaluated interface adhesion energy tends to be larger with the decreasing specimen size. With the result of electron backscattering diffraction analysis for Cu lines whose average grain size were 400nm diameter, it is suggested that local interface strength significantly varies depending on local grain distribution in a Cu interconnect structure.